Aerobic Development of Elite Youth Ice Hockey Players. Issue 11 (November 2015) - Leiter, Jeff R.; Cordingley, Dean M.; MacDonald, Peter B.
Abstract : Abstract: Leiter, JR, Cordingley, DM, and MacDonald, PB. Aerobic development of elite youth ice hockey players. J Strength Cond Res 29(11): 3223–3228, 2015—Ice hockey is a physiologically complex sport requiring aerobic and anaerobic energy metabolism. College and professional teams often test aerobic fitness; however, there is a paucity of information regarding aerobic fitness of elite youth players. Without this knowledge, training of youth athletes to meet the standards of older age groups and higher levels of hockey may be random, inefficient, and or effective. Therefore, the purpose of this study was to determine the aerobic fitness of elite youth hockey players. A retrospective database review was performed for 200 male AAA hockey players between the ages of 13 and 17 (age, 14.4 ± 1.2 years; height, 174.3 ± 8.5 cm; body mass, 67.2 ± 11.5 kg; body fat, 9.8 ± 3.5%) before the 2012–13 season. All subjects performed a graded exercise test on a cycle ergometer, whereas expired air was collected by either a Parvo Medics TrueOne 2400 or a CareFusion Oxycon Mobile metabolic cart to determine maximal oxygen consumption (V[Combining Dot Above]O2 max). Body mass, absolute V[Combining Dot Above]O2 max, and the power output achieved during the last completed stage increased in successive age groups from age 13 to 15 years ( p ⩽ 0.05). Ventilatory threshold (VT) expressed as a percentage of V[Combining Dot Above]O2 max and the heart rate (HR) at which VT occurred decreased between the ages of 13 and 14 years ( p ⩽ 0.05), whereas the V[Combining Dot Above]O2 at which VT occurred increased from the age of 14–15 years. There were no changes in relative V[Combining Dot Above]O2 max or HRmax between any successive age groups. The aerobic fitness levels of elite youth ice hockey players increased as players age and mature physically and physiologically. However, aerobic fitness increased to a lesser extent at older ages. This information has the potential to influence off-season training and maximize the aerobic fitness of elite amateur hockey players, so that these players can meet standards set by advanced elite age groups.